The Effect of the Proportion of Basil Leaf: Kenikir Leaf and Drying Time on the Physiochemical and Organoleptic of Herbal Tea Bag - Milenia Fitria Cholifah; Ulya Sarofa; M. Alfid Kurnianto (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Tea is a processed drink that is widely popular in the world. Tea contains many benefits, such as its antioxidant content, which fights free radicals. Kenikir leaves are a plant that has exceptionally high antioxidant activity. Basil leaves are an herbal plant with a distinctive fragrant aroma from its essential oils and many health benefits. This research aims to determine the effect of the proportion of basil leaves and kenikir leaves and the drying time on tea bags' physicochemical and organoleptic content. This research used a completely randomized design (CRD) with a factorial pattern with two factors and three replications. Factor I is the proportion of basil leaves: kenikir leaves (25:75,50:50,75:25), and factor II is the drying time (120 minutes, 150 minutes, 180 minutes). The data obtained were analyzed statistically using analysis of variance (ANOVA) followed by the Duncan Multiple Range Test (DMRT) at the 5% level. The best research results were obtained in the proportion of basil leaves and kenikir leaves of 25:75 with a drying time of 120 minutes producing tea bags with characteristics of water content of 7.79%, ash content of 6.2%, product antioxidant activity of 88.99%, the antioxidant activity of the brewed water was 73.31%, total phenols were 15.29 mg/GAE/g, flavonoids were 10.33 mgQE/g, and the color values L*, a*, b* were 45.97 respectively; 6.10; 21.70. With a color organoleptic characteristic value of 4.48 (Yellow); aroma of 3.52 (somewhat unpleasant); and taste of 3.48 (Slightly Bitter).